Model Matematika Dinamika Penyakit Pneumonia dengan Carriers - windi jelita; Defri Ahmad (Journal of Mathematics UNP, 2022)
Pneumonia disease is an infIammatory disease of the lungs (alveoli) caused by the bacterium Streptococcus pneumonia. When the body's immune system decreases, Streptococcus pneumonia will multiply and cause damage. Individuals colonized with Streptococcus pneumonia act as reservoirs for disease transmission. In Indonesia this disease is an endemic disease. In this study, a mathematical model is presented to describe the population of pneumonia in infants and toddlers. The purpose of this study was to determine the form of a mathematical model on the spread of disease, to know the results of the analysis and interpretation of the results of the analysis of the mathematical model of the spread of pneumonia with carriers. This research begins by determining the variables, parameters and assumptions related to the problem. The model that has been formed will then be analyzed. From the analysis obtained two fixed points, namely disease-free and endemic. From the results of the analysis, it was also obtained that the rate of individual contact could increase the spread of the spread of infected and infected individuals who were resistant to the body while being able to carry the spread of pneumonia